Are dry-land measurements and their asymmetries related to swimming performance? - Knihs, D. A.; Bishop, C.; da S. Athayde, M. S.; Gomes, E. W.; Pupo, J. D. (Sports Biomechanics, 2025)
This study aimed to verify the correlations between variables obtained from dry-land tests and swimming performance, in addition to examining the associations between the dry-land asymmetries and swimming performance. Thirty-seven male swimmers performed a test battery, including shoulder isokinetic torque, shoulder range of motion (ROM), vertical jump, anthropometric, and in-water force tests. Additionally, the best official performance in the events of 50 and 200 m front crawl was obtained. Interlimb asymmetries were calculated for all tested metrics, and Pearson and Spearman`s correlations were used to determine the association between the metrics (and their asymmetries) and swimming performance. Results showed that most of the dry-land metrics were significantly associated with 50 m front crawl (r = -0.59 to -0.83) and 200 m front crawl (r = -0.48 to -0.62) performance and with peak force at tethered swimming (r = 0.54 -0.80), except the ROM test (r = -0.22 -0.33). None of the asymmetries originating from the dry-land tests were significantly correlated with swimming performance (? = -0.29 -0.34). In conclusion, most dry-land outcomes measured are related to swimming performance, while the dry-land inter-limb asymmetries are not.